Thinking on screen : film as philosophy - Wartenberg, Thomas E. (London : Routledge, 2007)
Can philosophy be screened? -- Are there limits to film's philosophical capabilities? -- Illustrating a philosophical theory : Modern times -- A skeptical thought experiment : The matrix -- Arguing against utilitarianism : Eternal sunshine of the spotless mind -- Moral intelligence and the limits of loyalty : The third man -- Foregrounding the background : Empire and The flicker -- The nature of cinematic philosophy.
Includes bibliographical references and index.
Formerly CIP.
boek
Keywords: Philosophy in motion pictures